2016
DOI: 10.3390/en9100825
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Emissions from China’s Power Industry: Scenarios and Policies for 13th Five-Year Plan

Abstract: Abstract:The extended Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) model has been applied to analyzing the relationship between CO 2 emissions from power industry and the influential factors for the period from 1997 to 2020. The two groups found through partial least square (PLS) regularity test show two important areas for CO 2 emissions reduction from the power industry: economic activity and low-carbon electric technology. Moreover, considering seven influential factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…A stream of literature follows the STIRPAT model in the estimations. For example, Sun et al [30] investigated the determinants of CO 2 emissions from the power sector of China. They found the two most important factors which may help in pollution reduction that are electricity production with low carbon technology and economic activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A stream of literature follows the STIRPAT model in the estimations. For example, Sun et al [30] investigated the determinants of CO 2 emissions from the power sector of China. They found the two most important factors which may help in pollution reduction that are electricity production with low carbon technology and economic activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drivers influencing CO 2 emissions are classified under four headings. The first is population, represented by total population or urbanization level in earlier literature, which are found to be the contributory drivers of CO 2 emissions [27][28][29][30][41][42][43][44]. The second is affluence, usually reflected by gross domestic product (GDP) per capita.…”
Section: Stirpat Modelmentioning
confidence: 99%
“…In terms of China's power generation industry, Zhang [27] identified the determinants of CO 2 emissions change of the power sector in Beijing-Tianjin-Hebei region, and showed that the production sector's electricity intensity remains a critical factor for achieving CO 2 emission reductions. Sun et al [28] used a scenario analysis approach to estimate the CO 2 emissions in China's power industry for diverse scenarios, and derived policy implications based on the extended STIRPAT model. Wen et al [29] explored drivers of CO 2 emissions in China's power sector based on ridge regression and proposed related policy measures.…”
Section: Introductionmentioning
confidence: 99%
“…where A (1) and A (2) is the first and the second alternatives ranked by Q i . m is the number of evaluation alternatives…”
Section: Linguistic Variables Tfnsmentioning
confidence: 99%